Peningkatan Kenyamanan Pelanggan dengan Sistem Customer Relationship Management (CRM) - Yolla Rahmadi Helmi (Jurnal Sistim Informasi dan Teknologi, 2020)
In a business / company engaged in health both hospitals, clinics, practice requires something that can entice patients. In order to be comfortable and get facilities that can make patients loyal to treatment. One of the most supportive systems is the construction of an information system website that can facilitate patients and companies in carrying out their activities and can establish good communication and get reciprocal relationships between patients and doctors. Smile Dental Care is a dental clinic specializing in braces installation in the city of Padang, West Sumatra. The purpose of this research is to apply Customer Relationship Management (CRM) to improve the relationship between patients and doctors, so that they get comfortable with each other. The results of this study are the creation of an information system website, which is useful to support the improvement of Smile Dental Care, and provide excellent service to patients.